2006
DOI: 10.1038/sj.eye.6702649
|View full text |Cite
|
Sign up to set email alerts
|

Compressive optic neuropathy in fungal hypertrophic cranial pachymeningitis

Abstract: Sir, Compressive optic neuropathy in fungal hypertrophic cranial pachymeningitis We report a rare case of compressive optic neuropathy secondary to hypertrophic cranial pachymeningitis. Fungal aetiology is rarely reported in the literature and can be life threatening.Case report

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…3e6,9e76 3,6,10,12,13,15,22,23,25e27,29,32,33,39,44,45,47,52,54,56,58,63,76,78,79 PR as opposed to immunocompromised individuals (39%). 5,9,28,29,34,36,40,42,46,48,55,59,74 This difference might be explained by a more aggressive and acute course of the disease observed in immunosuppressed hosts. A culture-based diagnosis of Aspergillus meningitis is hampered by the lack of sensitivity as shown by the 31% of positive results observed in our review of published cases.…”
Section: Discussionmentioning
confidence: 99%
“…3e6,9e76 3,6,10,12,13,15,22,23,25e27,29,32,33,39,44,45,47,52,54,56,58,63,76,78,79 PR as opposed to immunocompromised individuals (39%). 5,9,28,29,34,36,40,42,46,48,55,59,74 This difference might be explained by a more aggressive and acute course of the disease observed in immunosuppressed hosts. A culture-based diagnosis of Aspergillus meningitis is hampered by the lack of sensitivity as shown by the 31% of positive results observed in our review of published cases.…”
Section: Discussionmentioning
confidence: 99%
“…Potential infectious causes include tuberculosis, syphilis, fungal infections, and sometimes bacterial infections. [1][2][3][4][5][6][7] Interestingly, there have been rare case reports identifying Staphylococcus spp. and Pseudomonas spp.…”
Section: Pachymeningitismentioning
confidence: 99%
“…Murai et al 4 reported a possible case of fungal pachymeningitis, which was not confirmed by dural biopsy. Ismail et al 5 reported a case in which a positive fungal culture was obtained from the frontal sinus, but they did not state clearly whether or not the fungal infection involved the meninges.…”
Section: Discussionmentioning
confidence: 99%